The Relationship of Kegel Exercise with Perineum Wound Healing In Postpartum Mothers at PMB Dince Safrina Pekanbaru - Rita Afni; Octa Dwienda Ristica (Science Midwifery, 2021)
During parturition, mothers experience many physical changes such as the abdominal wall becomes loose, the vaginal opening becomes loose and the pelvic floor muscles become loose. At the time of delivery, the mother may experience perineal laceration. Perineal laceration is a tear that occurs in the perineum during labor. Postpartum gymnastics is very good for mothers after giving birth, exercises that are applied during the postpartum period are Kegel exercises. Kegel exercises are exercises to strengthen the pelvic muscles, this exercise can be done immediately after giving birth to speed up and recovery of perineal wounds. This study aims to determine the relationship between Kegel exercises and perineal wound healing in postpartum mothers at PMB Dince Safrina Pekanbaru in 2021. The type of research conducted is quantitative with approach cross sectional study. Sampling in this study used a non-random sampling technique by purposive sampling. The population in this study isare postpartum mothers at PMB Dince Syafrina as many as 38 mothers giving birth. Analysis usedare univariate and bivariate. The results showed that there was a relationship between Kegel exercises and perineal wound healing in postpartum women. Expected toThe Independent Practice of Midwife Dince Syafrina, SST to be able to do Kegel exercises for postpartum women so that they can help heal perineal wounds, namely by introducing Kegel exercises to pregnant women through the provision of health education so that during the postpartum period they can do Kegel exercises and form classes for pregnant women to teach Kegel exercises to mothers. so that the mother is better prepared to carry it out during the puerperium